CAKUNG - PERTANIAN RAMAH LINGKUNGAN DIKAWASAN PERKOTAAN - Joshua Keeve Tandra; Suwandi Supatra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
In 2020, mankind throughout the world will be shaken by the Covid-19 which greatly affected people's lives and caused a lot of unrest. The Indonesian government implements a "at home" system. And with this regulation, many workers and factory workers have their salaries reduced, and some are given a termination policy even though they are still productive for work. So that the impact of Covid-19 will not only have an impact on health, the economy, but also on the workforce and also disrupt food security. The food sector is one of the sectors that is resilient in every crisis and as we know food is the main need of every society. Project "Eco-friendly Agriculture in the Cakung area" as a productive forum to accommodate the unemployed in the surrounding area due to layoffs so that they can get a job, learn, and improve their skills. Therefore this project is located in Cakung District, East Jakarta. This project is designed based on urban farming, which means farming in an urban environment using a hydroponic planting system for healthier production results. And through the results of field surveys and internet research, the site is close to PIK (Small Industry Center) which is an area that is a shopping center for people in the surrounding area which is dominated by the textile and food industry. So this building will also support the surrounding area, namely the PIK (Small Industry Center) by producing plants that can produce cloth fibers and also some staple and supporting foods that have fast harvest times so that they can produce quickly given the pandemic conditions that have resulted in increased demand. Therefore, this project is expected to minimize the issues raised. Keywords:  Covid-19; Urban Farming; Work Termination AbstrakTahun 2020 ini umat manusia diseluruh dunia digoncang dengan adanya pandemi Covid-19 yang sangat mempengaruhi kehidupan masyarakat dan menimbulkan banyak keresahan. Pemerintah Indonesia menerapkan sistem “dirumah aja”. Dan dengan adanya aturan ini membuat para pekerja dan buruh pabrik banyak yang dikurangi gajinya, dan beberapa diberi kebijakan Pemutusan Hubungan Kerja padahal masih produktif untuk bekerja. Sehingga dampak Covid-19 tidak hanya berdampak pada kesehatan, perekonomian, tetapi juga pada Tenaga Kerja dan juga mengganggu ketahanan pangan. Sektor pangan merupakan salah satu sektor yang tahan disetiap krisis dan seperti yang kita tahu pangan merupakan kebutuhan utama setiap masyarakat. Proyek “Pertanian Ramah Lingkungan dikawasan Cakung” sebagai wadah produktif untuk menampung para pengangguran dikawasan sekitar akibat PHK agar mereka mendapat pekerjaan, belajar, dan meningkatkan keterampilan mereka. Maka dari itu proyek ini berlokasi di Kecamatan Cakung, Jakarta Timur. Proyek ini dirancang berbasis urban farming yang dalam arti bercocok tanam dilingkungan perkotaan dengan menggunakan sistem tanam hidroponik agar hasil produksi lebih sehat. Dan melalui hasil survei lapangan dan riset internet, lokasi tapak berdekatan dengan PIK (Pusat Industri Kecil) yang merupakan area yang menjadi pusat perbelanjaan orang-orang dikawasan sekitar yang didominasi dengan industri tekstil dan makanan. Maka bangunan ini juga akan mendukung kawasan sekitar yaitu PIK (Pusat Industri Kecil) dengan memproduksi tanaman yang dapat menghasilkan serat kain dan juga beberapa makanan pokok dan pendukung yang memiliki waktu panen yang cepat agar dapat produksi dengan cepat mengingat kondisi pandemi yang mengakibatkan peningkatkan kebutuhan. Oleh sebab itu proyek ini diharapkan dapat menimalisir isu yang diangkat.